Effect of sulfate ions on growth and pollutants removal of self-flocculating microalga Chlorococcum sp. GD in synthetic municipal wastewater. (June 2017) - Lv, Junping; Guo, Junyan; Feng, Jia; Liu, Qi; Xie, Shulian
Highlights: Chlorococcum sp. GD grows well in sulfate-containing wastewater. Sulfate deprivation weakens growth, pollutants removal and flocculation. Sulfate deprivation decreases photosynthetic activity. Sulfate deprivation increases antioxidative enzymes activity. Sulfate deprivation affects cell activity via inducing reactive oxygen species. Abstract: Sulfate is a primary sulfur source and can be available in wastewaters. Nevertheless, effect of sulfate ions on growth and pollutants removal of microalgae seems to be less investigated. At the present study, self-flocculating microalga Chlorococcum sp. GD was grown in synthetic municipal wastewater with different sulfate concentrations. Results indicated that Chlorococcum sp. GD grew better in synthetic municipal wastewater with 18, 45, 77, 136 and 271 mg/L SO4 2− than in wastewater without SO4 2− . Chlorococcum sp. GD had also excellent removal efficiencies of nitrogen and phosphorus and effectively flocculated in sulfate wastewater. Sulfate deprivation weakened the growth, pollutants removal and self-flocculation of Chlorococcum sp. GD in wastewater. Antioxidative enzymes activity significantly increased and photosynthetic activity significantly decreased when Chlorococcum sp. GD was cultivated in sulfate-free wastewater. Sulfate deprivation probably reduced cell activity of growth, pollutants removal and flocculation via inducing the over-accumulation of reactive oxygen species (ROS).